Existence of Microchimerism in Pregnant Women Carrying a Boy! - Minai-Tehrani, Arash; Amini, Mehdi; Gilany, Kambiz (Journal of Reproduction & Infertility, 2016)
Microchimerism is considered as the occurrence of small populations of cells with a diverse genetic setting within a person. Tissue microchimerism is enhanced during pregnancy and is frequently associated with femaledominant autoimmune disorders, response to injury from malignancy, and transplantation effect.